Genome of a Gut Strain of Bacillus subtilis - Schyns, G. (2013)
Bacillus subtilis is a Gram-positive, rod-shaped, spore-forming bacterium. We present the genome sequence of an undomesticated strain, BSP1, isolated from poultry. The sequence of the BSP1 genome supports the view that B. subtilis has a biphasic lifestyle, cycling between the soil and the animal gastrointestinal tract, and it provides molecular-level insight into the adaptation of B. subtilis to life under laboratory conditions.